What is new in the treatment of advanced melanoma? State of the art - Mackiewicz, Jacek (Contemporary Oncology/Współczesna Onkologia, 2012)
The incidence of melanoma is increasing steadily both in Poland and worldwide. Until 2010 three drugs were approved for the treatment of metastatic melanoma – dacarbazine (DTIC) in Europe and USA, fotemustine in Europe and interleukin-2 (IL-2) in USA. Approval of ipilimumab and vemurafenib in Europe and USA has changed the standard of care, while the next candidates such as dabrafenib and trametinib have improved survival in phase III studies in metastatic melanoma patients. An encouraging treatment strategy is the combination of dabrafenib and trametinib, evaluated in a phase I/II study with an ongoing phase III trial. Another promising new immune modulating monoclonal antibody (mAb) is anti-PD1 (BMS-936558), tested in an early phase trial in monotherapy or in combination with a multipeptide vaccine in metastatic melanoma patients. Ipilimumab or BRAF inhibitors (vemurafenib, dabrafenib) seem to be active in patients with brain metastases. Intensive research of melanoma vaccines is currently being carried out in a number of countries worldwide. However, no vaccine in the treatment of melanoma has been approved by regulatory authorities so far. Lack of effective therapy in patients with high-risk resected melanoma led to a number of clinical studies of adjuvant treatment. Interferon- (INF-) therapy in this setting is still controversial. A dendritic cell-based vaccine in a randomized phase II trial showed a survival benefit over the control group in patients with high-risk resected melanoma. Promising results of long-term survival of advanced resected melanoma patients in a phase II study evaluating the genetically modified tumour vaccine (GMTV) AGI-101 were reported.